Pengaruh CAR, LDR, NIM, NPL dan BOPO Terhadap Kinerja Bank Umum di Indonesia (Studi Kasus pada Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Aditya Firmansyah Dimas Riadi; Ronny Malavia Mardani; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Non Performing Loans (NPL) and Operational Income Operating Costs (BOPO) on the performance of commercial banks in Indonesia ( case studies on banks listed on the Indonesia Stock Exchange in 2019-2021). The population in this study are all banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period with a total of 46 banking companies. The sampling technique using purposive sampling method obtained a sample of 31 banking companies. The research data collection method uses the data documentation method listed in the annual report at (IDX). The data analysis technique in this study used panel data regression with the eViews 9 software. The results showed that partially the Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) had a positive and significant effect on Return on assets (ROA). Loan to Deposit Ratio (LDR) has a positive and significant effect on Return on assets (ROA). Non Performing Loans (NPL) and Operating Costs Operating Income (BOPO) have a negative and significant effect on Return on assets (ROA) and sensitivity has a positive and significant effect on Return on assets (ROA). Keywords: CAR, LDR, NIM, NPL, BOPO, Return on assets (ROA)